Islamic Education Teachers' Strategies for Fostering Tolerance and Ukhuwwah Islamiyyah - Yan Fahmi Zuher; Suci Rahma Yuni; Denny Rusman; Muh Fauzi; Iswantir M (STIT Ahlussunnah Bukittinggi, 2026)
This study examines the strategies employed by Islamic Religious Education teachers to foster tolerance and ukhuwwah Islamiyyah (Islamic brotherhood) in school settings. The study is motivated by the growing need to strengthen harmonious social relations and mutual respect among students in increasingly diverse educational environments. Using a qualitative library research design with a content analysis approach, data were collected from scholarly journals, books, conference proceedings, and other relevant academic sources. The analysis involved data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that Islamic Religious Education teachers can promote tolerance and Islamic brotherhood through exemplary behavior, habituation of respectful interactions, collaborative learning activities, moral guidance, multicultural educational practices, and the integration of Islamic values derived from the Quran, Hadith, and exemplary narratives. The literature also highlights the importance of cultivating compassion, cooperation, deliberation, and social responsibility within the school community. These strategies contribute to the development of students' social and moral character, enabling them to respect diversity and maintain harmonious relationships. This study underscores the strategic role of Islamic Religious Education in fostering inclusive and value-based educational environments grounded in the principles of rahmatan lil alamin.